Therapeutic faecal microbiota transplantation controls intestinal inflammation through IL10 secretion by immune cells. Issue 1 (December 2018) - Burrello, Claudia; Garavaglia, Federica; Cribiù, Fulvia; Ercoli, Giulia; Lopez, Gianluca; Troisi, Jacopo; Colucci, Angelo; Guglietta, Silvia; Carloni, Sara; Guglielmetti, Simone; Taverniti, Valentina; Nizzoli, Giulia; et al.
Abstract Alteration of the gut microbiota has been associated with different gastrointestinal disorders. Normobiosis restoration by faecal microbiota transplantation (FMT) is considered a promising therapeutic approach, even if the mechanisms underlying its efficacy are at present largely unknown. Here we sought to elucidate the functional effects of therapeutic FMT administration during experimental colitis on innate and adaptive immune responses in the intestinal mucosa. We show that therapeutic FMT reduces colonic inflammation and initiates the restoration of intestinal homeostasis through the simultaneous activation of different immune-mediated pathways, ultimately leading to IL-10 production by innate and adaptive immune cells, including CD4+ T cells, iNKT cells and Antigen Presenting Cells (APC), and reduces the ability of dendritic cells, monocytes and macrophages to present MHCII-dependent bacterial antigens to colonic T cells. These results demonstrate the capability of FMT to therapeutically control intestinal experimental colitis and poses FMT as a valuable therapeutic option in immune-related pathologies. Faecal microbiota transplantation (FMT) is becoming a therapeutic option in several gastrointestinal disorders. Here, Burrello et al. study the immunological mechanisms by which FMT reduces colonic inflammation and initiates the restoration of intestinal homeostasis in a mouse model of colitis.